A Rare CD30+ Follicular B-Cell Lymphoma in a Female Child with Pulmonary Tuberculosis (PTB): A Case Report (Tanzania Medical Journal, 2025)
BackgroundFollicular lymphoma (FL) occurs in Tanzania but its CD30+ subtype is undocumented yet. Targeted immunotherapy for CD30+ Hodgkin lymphoma (HL) is available and consequently, its immunoreactivity in some non-Hodgkin lymphoma (NHL) may imply additional therapeutic benefit. Concomitant tuberculosis (TB) is rare but may have similar presentation.Case SummaryA 13-year-old female with recurrent, progressive left cervical lymphadenopathy was initially biopsied at Kilimanjaro Christian Medical Center (KCMC), diagnosed as undifferentiated carcinoma and pulmonary tuberculosis (PTB) and referred to Muhimbili National Hospital (MNH) where CD30+ follicular lymphoma was diagnosed and transferred to Ocean Road Cancer Institute (ORCI).DiscussionThis case, was associated with abundant CD45+, CD20+, CD30+ and CD3- neoplastic cells including Sputum positive PTB.Conclusion and recommendationThis CD30+ NHL is amenable to additional specific immunotherapy. Routine CD30 immunohistochemistry is recommended and concomitant TB be ruled-out.